Cybersecurity ethics an introduction - Manjikian, Mary (Abingdon, Oxon Routeldge, 2023)
"This textbook offers an accessible introduction to the topic of cybersecurity ethics. The second edition has been revised and updated, and contains new chapters on social justice, AI and big data. The book is split into three parts. Part I provides an introduction to the field of ethics, philosophy and philosophy of science, three ethical frameworks - virtue ethics, utilitarian ethics and communitarian ethics - and the notion of ethical hacking. Part II applies these frameworks to particular issues within the field of cybersecurity, including privacy rights, surveillance and intellectual property. The third part concludes by exploring current codes of ethics used in cybersecurity, with chapters on artificial intelligence, social diversity, big data and cyberwarfare. The overall aims of the book are to: - provide ethical frameworks to aid decision making; - present the key ethical issues in relation to computer security; - highlight the connection between values and beliefs and the professional code of ethics. The textbook also includes three different features to aid students: 'Going Deeper' features provide background on individuals, events, and institutions in cybersecurity; 'Critical Issues' features contemporary case studies; and 'Tech Talks', which contain features that assume some familiarity with technological developments. The book will be of much interest to students of cybersecurity, cyberethics, hacking, surveillance studies, ethics and information science"--
What is ethics?-- Three ethical frameworks-- The ethical hacker-- The problem of privacy-- The problem of surveillance-- The problems of intellectual property-- Ethics of Artificial Intelligence-- Cybersecurity, diversity, equity, and inclusion-- Big data and the ethics of cybersecurity-- Military aspects of cybersecurity ethics.
Includes bibliographical references and index.
Keywords: Computer crimes; Internet -- Moral and ethical aspects; Computer networks -- Security measures -- Moral and ethical aspects